Sokak çocuklarına yönelik din eğitimi etkinlikleri ve dini duygunun gelişimi (Cakarta örneği) - Nazıhah, Nazıhah (My University, 2024)
Araştırma, Cakarta'da sokak çocuklarına yönelik yaygın din eğitimi etkinliklerinin dinî duygunun gelişimi üzerindeki etkisini ortaya koymaktır. Cakarta'da sokak çocuklarına yönelik yaygın din eğitimi etkinlikleri gerçekleştirerek maddi-manevi alanda gelişmelerine katkı sağlayan kurumlar bulunmaktadır. Tasawuf Underground yatılı okulu, ERBE vakfı ve Sekolah Cendekia BAZNAS yatılı okulu tarafından yürütülen din eğitimi etkinlikleri kapsamında ilgilenilen 73 sokak çocuğunun inanç, ibadet ve ahlâk gibi dinî duygularının boyutları derinlemesine mülakat tekniği ile incelenmiştir. Araştırma sonuçlarına göre, din eğitimi aldıktan sonra sokak çocuklarında inanç, ibadet ve ahlaki anlamda pozitif gelişmeler tespit edilmiştir. Ayrıca kurumların düzenlediği din eğitiminin amacı, içeriği, yöntemi ve etkinlikleri de ortaya konulmuştur. Sonuçlardan esas alınarak bu alana özgü çalışmalar yapma, sokak çocuklarına yönelik din eğitimi etkinlikleri ile ilgili etik hususları inceleme, kanıta dayalı uygulama, program geliştirme ve politika güncelleme gibi önerilerde bulunulabilir.

There are institutions in Jakarta that carry out informal religious education programs aimed at street children, contributing to their material and spiritual well-being. The aim of the research is to reveal the impact of religious education activities for street children on the development of their religious sentiments. Within the scope of the religious education activities conducted by Tasawuf Underground boarding school, ERBE Foundation, and Sekolah Cendekia BAZNAS boarding school, the dimensions of religious sentiments such as belief, worship, and morality of 73 street children were examined through in depth interview techniques. Additionally, the purpose, content, method, and activities of the religious education organized by institutions have been revealed. According to the research results, after receiving religious education, street children's beliefs such as belief in Allah and belief in Prophet Muhammad have developed in accordance with religious beliefs. Moreover, it has been observed that street children perform their prayers and demonstrate morality in their daily lives. Based on the results, specific studies can be conducted in this field, and recommendations can be made regarding ethical issues, evidencebased practices, program development, and policy updates related to religious education activities for street children.
Religious education activity for street children and the development of religious sentiment (case of Cakarta)
Keywords: Cakarta; Cakarta (Endonezya); Cakarta (Indonesia); Din Eğitimi, Çocukların; Dinî Duygu Indonesia; Endonezya; Religious Education; Religious Education of Children; Religious Sentiment; Sokak Çocukları; Street Children; Yaygın Din Eğitimi